Contributions of the CGIAR Livestock and Climate Initiative to Kenya’s Third National Climate Change Action Plan (2023–2027) (NCCAP III) - Ng'ang'a, Kevin Gitau; Cramer, Laura K. (International Livestock Research Institute, 2024)
The third iteration of Kenya’s National Climate Change Action Plan (NCCAP III) for 2023-2027 outlines bold strategies for advancing low-carbon, climate-resilient development. This report validates the significant contributions of the Livestock and Climate Initiative to the NCCAP III, emphasizing its roles in facilitating workshops, guiding stakeholder input, and shaping the adaptation and mitigation priorities, livestock management strategies, and climate security frameworks. Drawing on insights from stakeholder interviews, workshop outcomes, and review of the NCCAP III final document, the report highlights the pivotal inputs enabled through the Initiative. The report synthesizes key insights drawn from a comprehensive review of NCCAP III, stakeholder interviews, and outcomes from multi-sectoral workshops that were conducted to shape its development. These engagements provided a platform for diverse voices, including government agencies, research institutions, civil society organizations, and local communities to contribute to the formulation of actionable strategies tailored to Kenya’s unique climate challenges. Additionally, the Livestock and Climate Initiative helped refine climate security frameworks within NCCAP III, ensuring that policies address both immediate and long-term risks associated with climate variability, droughts, and food insecurity. Their work has also supported the alignment of Kenya’s livestock and agriculture strategies with global climate commitments such as the Paris Agreement and the Sustainable Development Goals (SDGs).